MEWUJUDKAN SISTEM PERADILAN PIDANA YANG FAIR BAGI PENYANDANG DISABILITAS - Nur Patria, Eriq Panca (Mimbar Keadilan, 2022)
The purpose of this research is to analyze the legal protection for persons with disabilities who conflict with the law. The research was conducted using juridical-normative legal research. The results showed that the judiciary in Indonesia did not yet have a special mechanism. Such a situation certainly raises the question of what is the obligation of the State in providing protection and fulfillment of the rights of perpetrators and victims of persons with disabilities in a fair criminal justice process. The scope of citizens, in this case, is broad, including anyone without exception as stipulated in Article 25 paragraph (1) of the 1945 Constitution of the Republic of Indonesia that includes persons with disabilities. Affirmation of the scope is very important because human rights for persons with disabilities are still often ignored, even violated. The application of the principle of Equality Before the Law that persons with disabilities will have the same facilities as normal humans in accessing justice in the judiciary. The benefit is that persons with disabilities can easily convey their meaning and obtain justice so that the case can be resolved and it is easy to get information. Optimization, in this case, is also by the utility theory of Jeremy Bentham that "The aim of the law is the greatest happiness of the greatest number", namely the goal of the law is the greatest happiness for the most people.